The Pull And Roll Dermal Flaps: A Novel Technique For The Treatment Of Chronic Abdominal Wounds - Daou, B; Zogheib, S; Hanna, C; Sleilati, F (British Journal Of Surgical Science, 2025)
To our knowledge, this detailed above technique is not previously described and provides several advantages. It is simple to plan and perform, can be done under local anesthesia. It also avoids any undermining of the tissue which would expose the wound to tissue necrosis, dead space formation and fluid accumulation. The pull and roll dermal flaps reinforce midline fascial closure without the use of a synthetic mesh, seal and fill the dead spaces with viable tissue, Therefore reducing dehiscence, fluid accumulation, and infections.